Principles of Cost Accounting: Managerial Applications. - Anderson, Lane K.; Hendrickson, Harvey S. (The Accounting Review, 1987)
Reviews the book 'Principles of Cost Accounting: Managerial Applications,' 3rd ed., by Letricia Gayle Rayburn.